Ergot alkaloids--sources, structures and analytical methods - Flieger, M; Wurst, M; Shelby, R (Folia microbiologica, 1997)
Natural sources, i.e. fungal strains and species producing ergot alkaloids (EA), are surveyed together with the chemical structures of EA and a list of new natural EA discovered in the last three decades. Other topics include new efficient chromatographic methods (HPLC) for the separation and isolation of new natural EA and also immunological methods of EA detection.
Keywords: molekulární struktura; Chromatography, High Pressure Liquid; Immunoassay; Fungi; Molecular Structure; imunoanalýza; Ergot Alkaloids; houby; lidé; námelové alkaloidy; Humans; vysokoúčinná kapalinová chromatografie